Volume 1: Turbomachinery 1998
DOI: 10.1115/98-gt-260
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inlet Boundary Layer Thickness on the Flow Within an Annular S-Shaped Duct

Abstract: Experimental and numerical investigations were carried out to gain a better understanding of the flow characteristics within an annular S-shaped duct, including the effect of the inlet boundary layer (IBL) on the flow. A duct with six struts and the same geometry as that used to connect compressor spools on our experimental small two-spool turbofan engine was investigated. A curved downstream annular passage with a similar meridional flow path geometry to that of the centrifugal compressor has been fitted at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…Experimental measurements show that a large corner separation was formed between the strut and hub and the measured loss coefficient was Y p =0.090. [9] show that duct loss increases by 33% as the inlet boundary layer thickness is increased from 5% of span to 30%. Bailey et al [7] and Karakasis et al [10] show that including an upstream compressor stage increases duct loss; this is principally due to the presence of OGV wakes.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Experimental measurements show that a large corner separation was formed between the strut and hub and the measured loss coefficient was Y p =0.090. [9] show that duct loss increases by 33% as the inlet boundary layer thickness is increased from 5% of span to 30%. Bailey et al [7] and Karakasis et al [10] show that including an upstream compressor stage increases duct loss; this is principally due to the presence of OGV wakes.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Furthermore, the numerical results predicted higher losses near the hub owing to a large horse-shoe vortex formation. In further studies, 20 it was shown that the net total pressure losses are not significantly affected. However, the thicker inlet boundary layer notably affects the flow pattern in the S-duct.…”
Section: Introductionmentioning
confidence: 92%
“…These are deceptively simple geometries, but the flow patterns tend to be complicated as indicated in literature. [17][18][19][20][21] The flow develops under stream-wise alternating adverse and favourable pressure gradients and also under a radial pressure gradient. It is known that the hub wall is more susceptible to flow separation due to the curvature and an adverse pressure gradient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strut t/c 37% Splitter c/s 87% [9] show that duct loss increases by 33% as the inlet boundary layer thickness is increased from 5% of span to 30%. Bailey et al [7] and Karakasis et al [10] show that including an upstream compressor stage increases duct loss; this is principally due to the presence of OGV wakes.…”
Section: Number Of Struts 12mentioning
confidence: 99%